Interactions Investigation of New Composite Material Formed from Bauxite and Melamine-Urea Formaldehyde Copolymer - M. Radhi, Israa; I. Mohammed, Yousif; A. Himdan, Takialdin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study the Bauxite has been activated and used to prepare two complexes: Bauxite - urea and Bauxite - melamine, these complexes were merged and polymerized with formaldehyde to prepare the complex Bauxite polymer - urea - melamine - formaldehyde (modified Bauxite). In the Bauxite-urea complex XRD results indicate that the urea molecules penetrate among the layers of the crystal plane (110) of the Gibbsite mineral while in the Bauxite-melamine the interaction was at the outer surface of the Bauxite forming minerals because the relatively large volume of the melamine molecule. FT-IR results show the interaction of these two bases with Bauxite was mainly based on the hydrogen bonding and in less extent on the coordination between N loan pair atom and aluminum empty orbital in the above complexes. Finally the copolymer was formed around the micro-crystals of Bauxite minerals.